Pengaruh Kangoroo Mother Care terhadap Kualitas Tidur BBLR di RS Elpi Al Aziz Rantau Prapat - Rahmaini Fitri Harahap; Romawati Simanuntak; Rita Darmawati Silalahi; Lina Rotua Marbun (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
One of the biggest causes of LBW is premature birth before 37 weeks of gestation. Other causes of LBW include pregnancy complications, inadequate access to prenatal care, and poor nutrition. The purpose of this study was to determine the effect of Kangoroo Mother Care on LBW sleep quality. This type of research uses a quasi-experimental research design with pre-test and post-test with control group design. This research was conducted at Elpi Al Aziz Hospital Rantau Prapat. This study was conducted in August 2022. The population in this study were all LBW who were treated at Elpi Al Aziz Hospital. The sample in this study was 40 people consisting of 20 people in the control group and 20 people in the intervention group. Sampling in this study using purposive sampling technique. The data collection method used was the primary data collection of this research by observation and measurement. Secondary data was collected by looking at medical records (medical records). However, some secondary data was also carried out by interviewing some of the respondents' mothers. Data analysis used the Wilcoxon Rank test. The results obtained. Based on the Wilcoxon test, it was found that there was an influence between kangaroo mother care on the quality of LBW sleep with a p value of 0.000. The conclusion in this study is that there is an influence between kangaroo mother care on the quality of LBW sleep.